2009
DOI: 10.1373/clinchem.2008.106427
|View full text |Cite
|
Sign up to set email alerts
|

Reference Population and Marathon Runner Sera Assessed by Highly Sensitive Cardiac Troponin T and Commercial Cardiac Troponin T and I Assays

Abstract: BACKGROUND:Endurance exercise can increase cardiac troponin (cTn) concentrations as high as those seen in cases of minor myocardial infarction. The inability of most cTn assays to reliably quantify cTn at very low concentrations complicates a thorough data analysis, and the clinical implications of such increases remain unclear. The application of recently developed highly sensitive cTn immunoassays may help resolve these problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
208
2
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(233 citation statements)
references
References 37 publications
16
208
2
7
Order By: Relevance
“…In 2009, a gender-dependent difference in 99th URL for the highly sensitive cTnT assay (Roche Diagnostics) was also reported by Mingels et al [48] in a reference population of 479 apparently healthy individuals; the observed 99th percentile was 8 ng/L in 215 females, and 18 ng/L in 264 males. Results from larger studies [12,26] confirm the dependence of cTnT values on gender.…”
Section: Gendermentioning
confidence: 54%
See 2 more Smart Citations
“…In 2009, a gender-dependent difference in 99th URL for the highly sensitive cTnT assay (Roche Diagnostics) was also reported by Mingels et al [48] in a reference population of 479 apparently healthy individuals; the observed 99th percentile was 8 ng/L in 215 females, and 18 ng/L in 264 males. Results from larger studies [12,26] confirm the dependence of cTnT values on gender.…”
Section: Gendermentioning
confidence: 54%
“…Moreover, the method used to measure the troponin levels can affect results [25]: due to the low circulating levels of cTnI and cTnT in healthy subjects, only highly sensitive methods allow the accurate evaluation of biomarker variations in the majority of subjects tested, especially when pre-and post-exercise values are both below the 99th URL [8,25]. Importantly, almost 100% of subjects demonstrated a significant increase in circulating levels after exercise, especially when highly sensitive methods were employed [25,[52][53][54][55][56].…”
Section: Physical Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…The evidence that strenuous exercise can cause alterations in the metabolism and cardiovascular system are derived from several sporting events [2][3][4][5][6] . A meta-analysis of 26 studies demonstrated that troponin elevation occurs in approximately half of the participants of endurance tests, and this increase appears to be more common in shorter duration tests 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the emergence of hs-cTnT detection kits in clinical trials may facilitate the detection of hs-cTnT in patients with particular diseases, especially with an analytical range of 3-10,000 ng/L and coefficient of variation at 9% using the Elecsys e411 analyzer. The assay was specific for cTnT without interference from human cTnI, cTnC, skeletal muscle TnT, and hemoglobin concentrations up to 1,000 mg/L, above which false lower values could be expected (Mingels et al, 2009). The increase in hs-cTnT concentrations in normal controls is <1%, whereas these concentrations are increased significantly in patients with HF (Alehagen et al, 2010), diabetes mellitus, and ventricular hypertrophy due to unbalanced blood supply and demand.…”
Section: Discussionmentioning
confidence: 95%